2021
DOI: 10.51847/v4atuftzut
|View full text |Cite
|
Sign up to set email alerts
|

Mixed exposure to As, Mn, and Pb and dopamine neurotransmission in the striatum ‎

Abstract: This is an open access journal, and articles are distributed under the terms of the Creative Commons Attribution-Non Commercial-ShareAlike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as appropriate credit is given and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Additionally, a study from Saudi Arabia discovered that 117 patients (27%) in a cohort of 420 epilepsy patients had a positive family history of the disorder (Chentouf et al, 2015). Additionally, a casecontrol study in Algeria found that there was a 5.37-fold increased risk of having a first-degree relative with epilepsy (Lee et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a study from Saudi Arabia discovered that 117 patients (27%) in a cohort of 420 epilepsy patients had a positive family history of the disorder (Chentouf et al, 2015). Additionally, a casecontrol study in Algeria found that there was a 5.37-fold increased risk of having a first-degree relative with epilepsy (Lee et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…An epileptic seizure is a transient clinical sign and symptoms of abnormal, synchronous neuronal discharge reside in the cerebral cortex (Fisher et al, 2017;García, 2021;Lee et al, 2021;Mirghani et al, 2021). Epilepsy is clinically characterized by: two or more unprovoked (or reflex) seizures occurring more than 24 hours apart, or one unprovoked (or reflex) seizure and a probability of further seizures similar to the general recurrence risk (at least 60%) after two unprovoked seizures, occurring over the next ten years, or patient is already diagnosed as having epilepsy syndrome (Beretta et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Disorders of the cauda equina are etiologically and physically connected to the neuromuscular system in the spinal cord. A thorough history and neurological examination are necessary for clinical recognition of a cauda equinaaffecting condition, and to make a rapid diagnosis, the selection and interpretation of relevant neuroimaging investigations, neurophysiologic testing, and laboratory tests are necessary [1][2][3][4]. Cauda Equina Syndrome (CES) is hard to identify and treat illness.…”
Section: Introductionmentioning
confidence: 99%